Analisis Nilai Sosial dalam Cerita Rakyat Sendang Bidadari di Jepara - Silvia Maulinnikmah; Aurelia Cahya Fadhilatul Khalila; Osama Ahmad; Mohammad Kanzunnudin (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Indonesia has a very diverse cultural wealth, one of which is folklore that lives in various regions. Folklore, as a form of fiction originating from oral tradition, not only functions as entertainment, but also as a character education tool that conveys moral messages and social values. One of the famous folklores in Central Java, especially in Jepara Regency, is Sendang Bidadari. This story tells the origin of a spring that is a place for angels to stop and contains various social values ​​such as mutual cooperation, responsibility, politeness, honesty, and social concern. This study aims to identify the social values ​​contained in the Sendang Bidadari story and its meaning in the context of social life. Using a qualitative approach, this study analyzes the story to make it an alternative learning media in strengthening character education. The results of the study show that the Sendang Bidadari story can be used to teach the younger generation about the importance of preserving local culture and behaving well in social life.